The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s40265-016-0646-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy: Intuitive, Sound, Founded…But Not Broadly Applied

Abstract: Circadian rhythms are a collection of endogenously driven biochemical, physiological, and behavioral processes that oscillate in a 24-h cycle and can be entrained by external cues. Circadian clock molecules are responsible for the expression of regulatory components that modulate, among others, the cell’s metabolism and energy consumption. In clinical practice, the regulation of clock mechanisms is relevant to biotransformation of therapeutics. Accordingly, xenobiotic metabolism and detoxification, the two pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 93 publications
0
43
0
Order By: Relevance
“…This concept is referred to as chronotherapy [96,97]. Despite the solid mechanistic basis, the concept is not broadly exploited in ongoing clinical trials [98]. Correctly estimating chronotype using logistically feasible methods is essential for chronotherapy efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is referred to as chronotherapy [96,97]. Despite the solid mechanistic basis, the concept is not broadly exploited in ongoing clinical trials [98]. Correctly estimating chronotype using logistically feasible methods is essential for chronotherapy efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, food components may interact with epigenetic factors with powerful protective and preventive potentials against inflammation in aging and age-related diseases [18]. Moreover, circadian rhythms have profound effects on xenobiotic metabolism and detoxification processes [19]. However, even with strong evidences, chronotherapy including the 'time-of-day' administration still needs more attention for personalized therapeutic regimens to reduce adverse effects and promote the efficacy [3,19].…”
Section: Editorial Yanmentioning
confidence: 99%
“…Moreover, circadian rhythms have profound effects on xenobiotic metabolism and detoxification processes [19]. However, even with strong evidences, chronotherapy including the 'time-of-day' administration still needs more attention for personalized therapeutic regimens to reduce adverse effects and promote the efficacy [3,19].…”
Section: Editorial Yanmentioning
confidence: 99%
“…The numerous connections between the circadian clock and skeletal homeostasis bring about the possibility of targeting circadian rhythms to improve existing therapies and develop new routes. One approach is to adopt the concept of 'chronotherapy', in which the drug regimen is tailored to a patient's circadian rhythm in order to maximise treatment effectiveness and reduce adverse effects (Selfridge et al 2016). Over 40 years ago, it was reported that OA and RA symptoms can be improved by timing the intake of indomethacin and flurbiprofen; and treatment efficiency was correlated with the individual circadian variation of pain (Huskisson et al 1970, Kowanko et al 1981, Levi et al 1985.…”
Section: Clinical Relevance Of Circadian Biology For Skeletal Disordersmentioning
confidence: 99%